Reliability study of high-κ La2O3/HfO2 and HfO2/La2O3 stacking layers on n-In0.53Ga0.47As metal–oxide–semiconductor capacitor. (22nd January 2016) - Chu, Chung-Ming; Lin, Yueh-Chin; Lee, Wei-I; Dee, Chang Fu; Wong, Yuen-Yee; Majlis, Burhanuddin Yeop; Salleh, Muhamad Mat; Yap, Seong Ling; Chang, Edward Yi
Abstract: This study investigates the time-dependent dielectric breakdown (TDDB) characteristics of La2 O3 /HfO2 and HfO2 /La2 O3 stacking layers on an n-In0.53 Ga0.47 As metal–oxide–semiconductor capacitor. Both designs improved the reliability compared with a single layer of HfO2 . The TDDB followed the thermochemical E model. The current transportation mechanism changed from thermionic emission to Frenkel–Poole emission because of the traps creation under voltage stress. Both designs resulted in similar lifespans and voltage accelerating factors. However, the La2 O3 /HfO2 design had a longer lifespan because of the lower interface trap density and insertion of the HfO2 diffusion barrier layer between La2 O3 and n-In0.53 Ga0.47 As. The oxide stacks exhibited excellent reliability and achieved a lifespan of 28.4 years.